MEMBANGUN DAN MENGELOLA KAWASAN PERBATASAN: MENJAGA KEUTUHAN DAN MEMPERTAHANKAN KEDAULATAN INDONESIA - Tundjung Herning Sitabuana (Faculty of Law, Universitas Diponegoro, 2015)
Indonesia should be able to maintain its territorial integrity and its sovereignty, including parts of Indonesia border. The problem is not just to set of and affirmed the border line but how to put the border region as part of Indonesian territory. Efforts to preserve and defend the territorial integrity of Indonesia should be based on the paradigm of welfare (through development and education), and the paradigm of security (to provide protection to the citizens who live in the border area, and to provide protection and supervision of the Indonesian territory in the border area). Development and management of Indonesian territory in the border area should be done in an integrated and sustainable way.